2022
DOI: 10.1177/20503121221107337
|View full text |Cite
|
Sign up to set email alerts
|

Self-care practices and correlates among patients with type 2 diabetes in Eastern Ethiopia: A hospital-based cross-sectional study

Abstract: Objective: This study investigated the level and correlates of self-care practices among patients with type 2 diabetes on follow-up in two public hospitals in Harar, Eastern Ethiopia. Methods: We conducted a hospital-based cross-sectional study on adult patients with type 2 diabetes, surveying diabetes self-care practices using a 15-item Summary of Diabetes Self-Care Activities. Responses ranged from 0 to 7 days, and a composite score was computed representing the mean days of diabetes self-care practices. A g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…This might be partly explained by the fact that patients who experienced hospitalizations secondary to diabetes might become more conscious of the benefits of daily self-care activities to prevent further complications and hospitalizations. It is important to note, however, that other studies have found that hospitalizations are inversely correlated with self-care activities [30,31]. Furthermore, having asthma or other respiratory diseases was found to be associated with lower levels of self-care activities.…”
Section: Discussionmentioning
confidence: 73%
“…This might be partly explained by the fact that patients who experienced hospitalizations secondary to diabetes might become more conscious of the benefits of daily self-care activities to prevent further complications and hospitalizations. It is important to note, however, that other studies have found that hospitalizations are inversely correlated with self-care activities [30,31]. Furthermore, having asthma or other respiratory diseases was found to be associated with lower levels of self-care activities.…”
Section: Discussionmentioning
confidence: 73%
“…This is sensible because a negative attitude towards self-care weakens beliefs about the expected benefits and healthy behaviors 44 . Moreover, these findings could be attributed to a lack of formal diabetes education, which can influence attitudes toward diabetic self-care behaviors 19,45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…51 Patients should learn about self-care methods and approaches to handle elevated blood sugar levels while having care in the hospital. 52 Patients can significantly manage hyperglycemia after surgery by actively engaging in care. Open communication, adherence to medical advice and a proactive approach to monitoring and selfcare play vital roles in ensuring a successful recovery.…”
Section: Symptoms Management Strategiesmentioning
confidence: 99%
“…Nutritional management by considering proper nutrition can help support healing and reduce the risk of TURP complications such as long‐term hyperglycemia 51 . Patients should learn about self‐care methods and approaches to handle elevated blood sugar levels while having care in the hospital 52 . Patients can significantly manage hyperglycemia after surgery by actively engaging in care.…”
Section: Symptoms Management Strategiesmentioning
confidence: 99%